The Crescent and the Cross
XI, 234 p.
Keywords: This book is the product of dialogue between a group of leading British Muslim and Christian scholars concerned about the alleged danger to the 'West' of Islamic 'fundamentalism'. It analyses the ethical and legal principles, rooted in both traditions, underlying any use of armed force in the modern world. After chapters on the history, theology and laws of war as seen from both sides, the book applies its conclusions to (a) the 1990-91 Gulf War and (b) the Bosnian Conflict. It concludes that Huntington's 'Clash of Civilisations' thesis is a dangerous myth.